Pendidikan kesehatan dengan media pop-up meningkatkan pengetahuan gizi seimbang siswa sekolah dasar - Permatasari, Firlya Sanafa; Rahmawati, Agustina; Isnaeni, Yuli (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Elementary school children are in a growth and development phase and require balanced nutrition. Lack of knowledge can lead to nutritional problems such as undernutrition and overnutrition. Health education using engaging media can improve children's knowledge of balanced nutrition. Purpose: To determine the effect of health education using the "Giziku" pop-up media on elementary school students' knowledge of balanced nutrition. Method: This quantitative, quasi-experimental study used a pretest-posttest control group design. Fifty-seven students were recruited using a total sampling technique. Data were collected using a knowledge questionnaire and tested using the Mann-Whitney test. Results: This study found a difference in knowledge levels between the treatment and control groups with a p-value (0.000 < 0.05). Conclusion: There is an effect of health education using the "Giziku" pop-up media on elementary school students' knowledge.   Keywords: Balanced Nutrition; Health Education; Knowledge; Pop-Up Media.   Pendahuluan: Anak sekolah dasar merupakan anak yang sedang berada pada tahap tumbuh kembang dan memerlukan kebutuhan gizi yang seimbang. Kurangnya pengetahuan dapat menyebabkan masalah gizi seperti gizi kurang dan kelebihan gizi. Pendidikan kesehatan dengan media yang menarik dapat meningkatkan pengetahuan gizi seimbang pada anak. Tujuan: Untuk mengetahui pengaruh pendidikan kesehatan dengan media pop-up “Giziku” terhadap pengetahuan gizi seimbang siswa sekolah dasar. Metode: Penelitian kuantitatif quasi experiment dengan rancangan with control group pretest-posttest. Responden terdiri dari 57 siswa dan diambil dengan teknik total sampling. Pengumpulan data menggunakan kuesioner pengetahuan serta di uji menggunakan uji Mann Whitney. Hasil: penelitian ini terdapat perbedaan tingkat pengetahuan pada kelompok perlakuan dan kelompok kontrol dengan p-value (0,000 < 0,05). Simpulan: Ada pengaruh pendidikan kesehatan dengan media pop-up “Giziku” terhadap pengetahuan siswa sekolah dasar.   Kata Kunci: Gizi Seimbang; Media Pop-Up; Pendidikan Kesehatan; Pengetahuan.